2015
DOI: 10.1186/s13148-015-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

Inter-locus as well as intra-locus heterogeneity in LINE-1 promoter methylation in common human cancers suggests selective demethylation pressure at specific CpGs

Abstract: BackgroundHypomethylation of long interspersed element (LINE)-1 has been observed in tumorigenesis when using degenerate assays, which provide an average across all repeats. However, it is unknown whether individual LINE-1 loci or different CpGs within one specific LINE-1 promoter are equally affected by methylation changes. Conceivably, studying methylation changes at specific LINE-1 may be more informative than global assays for cancer diagnostics. Therefore, with the aim of mapping methylation at individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 42 publications
2
41
0
1
Order By: Relevance
“…() (c), and Nüsgen et al. () (d); the bracket labeled “a” indicates the CpG‐sites covered by the PyroMark LINE ‐1 kit (Qiagen, Hilden, Germany). (A) Summary of significant differences between tumor and healthy neighboring tissue (*,**, and *** correspond to significant values of p < 0.05, <0.005, and <0.0005); n: nonsignificant; based on data in Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…() (c), and Nüsgen et al. () (d); the bracket labeled “a” indicates the CpG‐sites covered by the PyroMark LINE ‐1 kit (Qiagen, Hilden, Germany). (A) Summary of significant differences between tumor and healthy neighboring tissue (*,**, and *** correspond to significant values of p < 0.05, <0.005, and <0.0005); n: nonsignificant; based on data in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in a comparison of multiple cancer types, Nüsgen et al. () observed that tumors could be ranked by their LINE‐1 hypomethylation levels with urinary bladder cancers being most hypomethylated followed by prostate, colon, and stomach cancers. The mechanism underlying the preferential hypomethylation in certain cancer types are still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation profiles within specific genes can affect their transcriptional patterns and can be altered by exogenous stressors. Given that DNA hypermethylation-induced silencing of tumor-suppressor genes and hypomethylation-induced activation of oncogenes have been described in virtually all human cancers and are considered driving mechanisms of carcinogenesis (Portela & Esteller, 2010; Heyn & Esteller, 2012; Jones, 2012; Johnson et al, 2015; Nüsgen et al, 2015), the potential for IR-induced changes in gene-specific DNA methylation that affect changes in expression are critically important.…”
Section: Ionizing Radiation and Gene-specific Dna Methylationmentioning
confidence: 99%
“…Barry et al 32 reported Alu hypermethylation in blood of patients with prostate cancer. Additionally, both hypomethylation and hypermethylation of LINE-1 CpGs were detected in the blood of patients with pancreatic, colon, and gastric cancer 33. Taken together, these recent reports demonstrate that the pattern of LINE-1 methylation in blood is quite variable, in a clear contrast to tumor samples, which in general exhibit a genome-wide hypomethylation.…”
Section: Discussionmentioning
confidence: 68%